2004
DOI: 10.1016/j.solener.2003.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of window blinds on daylight-linked dimming and automatic on/off lighting controls

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(27 citation statements)
references
References 3 publications
0
21
0
4
Order By: Relevance
“…In the Canadian climate, Galasiu et al (2004) tested different combinations of lighting and shading control systems. For the electric lighting, the authors used dimmable and on/off daylight systems, which were combined with photo controlled blinds as well as with different cases of static positions of the blinds.…”
Section: Daylight-linked Control Systemsmentioning
confidence: 99%
“…In the Canadian climate, Galasiu et al (2004) tested different combinations of lighting and shading control systems. For the electric lighting, the authors used dimmable and on/off daylight systems, which were combined with photo controlled blinds as well as with different cases of static positions of the blinds.…”
Section: Daylight-linked Control Systemsmentioning
confidence: 99%
“…On/off and continuous dimming controls are two commonly used daylight linked control systems. Previous studies showed that both of the control systems can reduce electrical lighting energy consumption significantly in the buildings that have indoor daylight access [45][46][47][48][49][50][51]. However, the on/off control system requires extra attention to adequate zoning and its calibration (based on space daylight availability) [46].…”
Section: Lighting Controlmentioning
confidence: 99%
“…In a high latitude region, a study conducted experiments in real offices to measure the workplane daylight illuminance from double glazed windows with horizontal slats and the resultant power consumption from dimmable light lamps [2]. The results showed that the interior daylight is influenced largely by tilted angle of the slats, varying sky conditions, and sun position relating to window orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Energy savings from lighting depended on types of controls by which the continuous dimming offered in most cases higher savings than the automatic on/off. Other studies conducted daylight simulations to achieve optimal configuration and tilted angle of the slats on window [2]. Studies of windows with slats have involved in modeling of the daylight transmission.…”
Section: Introductionmentioning
confidence: 99%